2018
DOI: 10.1002/1878-0261.12386
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transcriptional regulation of PIAS3 expression by miR‐18a in malignant mesothelioma

Abstract: Protein inhibitor of activated STAT3 (PIAS3) is an endogenous suppressor of signal transducer and activator of transcription 3 (STAT3) signaling. By directly interacting with phosphorylated STAT3, PIAS3 can block the downstream transcriptional activity of STAT3, which is hyper‐activated in various cancers. We previously reported that in malignant mesothelioma (MM), low PIAS3 expression is associated with increased STAT3 activation and correlates with poor patient survival, yet the regulatory mechanism(s) gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Zhang et al reported that miR-18a exerts its oncogenic function by regulating the PTEN-PI3K-AKTmTOR signaling axis to improve Cyclin D1 expression and further accelerate cell cycle progression of esophageal squamous cell carcinoma cells [37]. Likewise, miR-18a was found to upregulate PIAS3 expression at the post-transcriptional level to facilitate malignant mesothelioma cell growth [38]. Besides, the deficiency of miR-18a was discovered to improve cisplatin sensitivity to non-small cell lung cancer cells by targeting PTEN [39].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that miR-18a exerts its oncogenic function by regulating the PTEN-PI3K-AKTmTOR signaling axis to improve Cyclin D1 expression and further accelerate cell cycle progression of esophageal squamous cell carcinoma cells [37]. Likewise, miR-18a was found to upregulate PIAS3 expression at the post-transcriptional level to facilitate malignant mesothelioma cell growth [38]. Besides, the deficiency of miR-18a was discovered to improve cisplatin sensitivity to non-small cell lung cancer cells by targeting PTEN [39].…”
Section: Discussionmentioning
confidence: 99%
“…The function of miR‐18a as a suppressor of PIAS3 was also identified in malignant mesothelioma (MM) [66]. The referenced study screened candidate miRNAs in MM cell lines with low PIAS3 expression and conducted luciferase reporter assays to validate the regulation via the 3′‐UTR of PIAS3.…”
Section: Main Textmentioning
confidence: 99%
“…In our previous comprehensive analysis of miRNA expression by RT-qPCR using TaqMan Low Density Array Human miRNA Cards, both miR-18a-3p and miR-18a-5p were upregulated in malignant mesothelioma cell lines (ACC-MESO1, ACC-MESO4, CRL-2081, CRL-5820, CRL-5826, CRL-5915, and CRL-5946) compared to non-neoplastic mesothelial tissues (11). He et al (26) found that miR-18a-5p promoted mesothelioma cell proliferation by downregulating PIAS3, but little is known about the function of miR-18a-3p in mesothelioma cells. In the present study, we showed that inhibition of miR-18a-3p reduced proliferation and migration, but increased apoptosis of mesothelioma cells.…”
Section: Discussionmentioning
confidence: 99%